Drought weakens greenhouse gas sink of global wetlands - Longxin Qiao; Xinxin Wang; Hongyang Chen; Jihua Wu; Xiangming Xiao; Ming Nie; Rui-Ting Ju; Yuhan Zheng; Xi Zhang; Qiang He; Xutong Ru; Lijuan Cui; et al. (Environmental Impact Assessment Review, 2027)

Stratigraphy, sedimentology, and palaeoenvironment of dinosaur-bearing Upper Cretaceous Zhengyang Formation in Zhengyang Basin, Chongqing, Southwest China - Hui Dai; Jun Wang; Liang-Dong Luo; Qian-Ru Wen; Su-Chin Chang; Yu Lin; Ming Xiao; Hai Xing (Palaeoworld, 2026)

Paternal vitamin D deficiency is associated with offspring testicular developmental abnormalities, fibrosis, and altered sperm miRNA profiles - Yu-Ming Chen; Zhi-Hong Tian; Shi-Yuan Li; Juan Dai; Xing-Ru Wang; Guo-Ying Sun; Min Liu; Berthold Hocher; Mei Tian (Molecular Biology Reports, 2026)

Differential roles of three subclass III C6 transcription factors in the insect-pathogenic lifecycle of Beauveria bassiana - Jian-Ru Feng; Min Li; Sheng-Hua Ying; Ming-Guang Feng (Journal of Invertebrate Pathology, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Unveiling an entirety of TFIIH complex comprising Tfb3, Kin28 and Ccl1, and anti-UV and insecticidal activities of Ccl1 in Beauveria bassiana - Min Li; Jian-Ru Feng; Sheng-Hua Ying; Ming-Guang Feng (Pesticide Biochemistry and Physiology, 2026)

Microbial and metabolomic analyses elucidate the Debaryomyces hansenii-mediated flavor enhancement in dry-aged black pig pork - Ruo-Chun Kao; Meng-Ru Lee; Rung-Jen Tu; Wen-Shyan Chen; Hsiao-Mei Liang; Hsiu-Ming Liu; Hsin-Hui Su; Yen-Po Chen; Yung-Tsung Chen (Food Microbiology, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Different mucosal immunity and hormonal responses to routine physical training in the follicular and the luteal phases of elite female athletes - Chung-Kai Wang; Cheng-Shiun He; Ming-Ru Chiang; Pei-Ying Li; Chun-Wei Wang; Liang-You Chen; Shih-Hua Fang (European Journal of Applied Physiology, 2026)

Paedocin A: An undescribed iridoid with a C1-C4 ether linkage from Paederia foetida with hepatoprotective effects - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry Letters, 2026)

Design optimization of plate anchor for offshore foundation systems - Ru-Ming Feng; Meysam Bayat; Liyun Zhu; Lei Tan (Marine Georesources & Geotechnology, 2026)

Genomics-guided exploration of Nesterenkonia sp. CL21 proteases to produce bioactive peptides with antioxidant and α-amylase inhibitory activities from soy sauce cake hydrolysis - Shieh Feng Chen; Cyn Ru Cheah; Ivan Kai Jie Lim; Hongxuan An; Chun Shiong Chong; Ming Quan Lam; Kah Yaw Ee (Food Bioscience, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Experimental study on interaction of track and clayey seabed for deep-sea mining vehicles - Bo-Wen Chen; Ru-Ming Feng; Chao Hou; Wei-Qiang Feng (Ocean Engineering, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Characterization of a new isolate of tomato zonate spot virus from Vaccinium uliginosum L. in China - Yueyan Yin; Tao Lin; Ru Dong; Zhijiao He; Jing Zhong; Liling Zhao; Jiawei He; Ming Ding; Tingting Li (Journal of Plant Pathology, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Dual-functional eggshell-derived system for comprehensive phosphorus recovery from agricultural wastewater: From laboratory validation to pilot-scale implementation - Qiao Wu; Maoqing Fan; Xiaoyu Zheng; Ming Zeng; Saihong Ru; Chengyou Sun; Chao Huang (Bioresource Technology, 2026)

Coronary CT Angiography-Based Prediction Model for Hemodynamically Significant Coronary Stenosis Integrating Morphological and Plaque Characteristics - Chenxi Wang; Shuang Leng; Ru-San Tan; Ping Chai; Jiang Ming Fam; Adrian Fatt Hoe Low; Lohendran Baskaran; Lynette Teo; Felix Yung Jih Keng; Chee Yang Chin; Ching Ching Ong; John C. Allen; et al. (Cardiovascular Engineering and Technology, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

Comparative roles of four TFIIH subunits (Tfb1, Tfb2, Tfb4 and Tfb5) in anti-UV and insecticidal processes of Beauveria bassiana - Min Li; Jian-Ru Feng; Sheng-Hua Ying; Ming-Guang Feng (Pesticide Biochemistry and Physiology, 2026)

Cyclopentanoid monoterpene glycosides from the aerial parts of Paederia foetida L - Wan-Qi Zhang; Xin-Yue Li; Ming-Hui Sun; Jie Zhou; Guo-Ru Shi; De-Quan Yu; Yan-Fei Liu (Phytochemistry, 2026)

Flexible and anti-freezing eutectogel for high-performance ionotronic sensors - Ping Gan; Yi-Jun Cao; Ming-Ru Xie; Hui-Ping Chen; Chun-Fang Xie; Jie-Ping Fan (Chemical Engineering Journal, 2026)

Association between magnesium sulfate administration and mortality in critically ill patients with sepsis-associated acute kidney injury: a retrospective propensity score-matched cohort study - Xiang-Jie Duan; Jing-Ru Lan; Ming-Gao Zhu; Jin-Lian Chen; Chang-Yun Zhang; Hai-Yan Yin; Wan-Jie Gu (European Journal of Clinical Pharmacology, 2026)

Short-duration electrical pulse stimulation induces myokines and mitochondrial adaptations in C2C12 myotubes - Shih-Hua Fang; Ming-Ru Chiang; Chia-Yang Li; Pei-Ying Li; Zong-Jia Wu; Hsin-Hua Li (Journal of Muscle Research and Cell Motility, 2026)

Regulatory roles of three Zn(II)2Cys6 cluster-coding genes in insect pathogenicity and environmental fitness of Beauveria bassiana - Jian-Ru Feng; Min Li; Sheng-Hua Ying; Ming-Guang Feng (Pesticide Biochemistry and Physiology, 2026)

Spatio-seasonal distribution, precursor transformation, and ecological risks of per- and polyfluoroalkyl substances in port sediments: Insights from a subtropical urban harbor - Chih-Feng Chen; Noralyn G. Dimaongon; Yun-Ru Ju; Chiu-Wen Chen; Yee Cheng Lim; Ming-Huang Wang; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Integrated assessment of trace element enrichment and accumulation in estuarine sediments of southwestern Taiwan using Sr/Ba ratios and pollution indices - Chih-Feng Chen; Noralyn G. Dimaongon; Yee Cheng Lim; Ming-Huang Wang; Yun-Ru Ju; Kent Naiah D. Araña; Chiu-Wen Chen; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Changes in tree composition and diversity of streetscapes and their impact on allergenic risk of pollen during urban expansion: a case study in Chengdu, China - Ming-kun Chen; Zhen-ru Yang; He Li; Hua Zong; Chen Jiao (Landscape and Urban Planning, 2026)

Dual-dynamic polyimide and its thermally conductive adhesive featuring high glass transition temperature, recyclability, and strong adhesion - Fang Li; Ping Yu; Bin Wu; Ming Cao; Ru Xia; Jiasheng Qian (Chemical Engineering Journal, 2026)

Automated modal identification of offshore wind turbines via an uncertainty-quantified stochastic subspace method - Jing Song; Kang Zhou; Zhen-Ru Shu; Xiao-Ying Cai; Ming-Gang Duan (Ocean Engineering, 2025)

Seasonal and spatial variation, and land-use influences on riverine microplastics and their ecological risks in the Yanshui River Basin - Yi-Wei Biao; Hong-Ming Zheng; Wan-Ru Chen (Journal of Environmental Chemical Engineering, 2025)

Machine learning-enhanced prediction of size-resolved gas-particle partitioning quotient: Implication for health risk assessment of polycyclic aromatic hydrocarbons - De-Qi Wang; Wan-Li Ma; Ru-Peng Wang; Pu-Fei Yang; Peng-Tuan Hu; Shi-Ming Jia; Meng Qin (Journal of Hazardous Materials, 2025)

A novel thermophilic α-glucan phosphorylase enables molecular weight-tunable amylose biosynthesis from cellobiose via a dual-enzyme cascade system - Wei Gao; Ru Yang; Mengli Li; Ming Miao; Tao Zhang (Food Bioscience, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Analysis of the synchronous enhancement in CO2 sequestration by steel slag using steam in flue gas: performance and mechanism - Shuang Wang; Yi-fei Zhang; Kai Zhao; Hong-ming Long; Ru-fei Wei (Journal of Cleaner Production, 2025)

Nano architectonics via in situ growth of MIL-101(Fe) on modified sugarcane bagasse for selective capture of glyphosate from aqueous solution - Ru-yi Zhou; Ming-hua Liu; Yun Xiao; Yu Qin; Bo Zuo; Muhammad Akhtar Abbas; Jun-xia Yu; Xiao-di Li; Yue-fei Zhang; Ru-an Chi (Journal of Environmental Chemical Engineering, 2025)

The threat of microplastics to human kidney health: Mechanisms of nephrotoxicity and future research directions - Ru-Yu Tan; Qin-Ying She; Yun-Ci Ma; Ming-Hong Liu; Li-Juan Li; Li-Li Huang; Yi-Wen Zhong; Hui-Xin Bi (Environmental Research, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Reprocessable cross-linked EPDM elastomers with dynamic and tuneable imine network based on electronic effect - Zhongyang Liu; Ming Cao; Haoran Liu; Bin Wu; Jibin Miao; Youfeng Tian; Yuchao Ke; Ru Xia; Jiasheng Qian (Chemical Engineering Journal, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Tongxinluo alleviates myocardial ischemia–reperfusion injury by inhibiting the pyroptosis of endothelial cells via the NLRP3/Caspase-1/GSDMD signaling pathway - Xuan Wu; Yun-long Hou; Tong-xing Wang; Li-ping Chang; Hong-ru Zhou; Ming-ye Wang; Yi-ling Wu (Journal of Molecular Histology, 2025)

Anti-inflammatory and antinociceptive effects, toxicity, and phytochemical analysis of Beaumontia grandiflora Wall. - Rui Yang; Dan Teng; Ming-rui Yang; Yi-huan Li; Jian-fen Xiao; Qian-ru Zhang; Hong-ping He; Hua-yi Jiang (Natural Product Research, 2025)

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Cross-view geo-localization with panoramic street-view and VHR satellite imagery in decentrality settings - Panwang Xia; Lei Yu; Yi Wan; Qiong Wu; Peiqi Chen; Liheng Zhong; Yongxiang Yao; Dong Wei; Xinyi Liu; Lixiang Ru; Yingying Zhang; Jiangwei Lao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

The effect of ligand regulation on mechanism of alkaline oxygen evolution reaction under industrial scale - Xin-Ru Li; Xue-Jun Zhai; Hao-Zheng Liu; Xin Wen; Yanbin Qi; Chen Zhang; Guodong Li; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2025)

Construction and optimization of low carbon-to-nitrogen ratio-adapted Chlorococcum-Bacteria symbiosis for energy-efficient wastewater remediation - Ru Yan; Han Ji; Zhuo-Chao Liu; Mei-Qi Ren; Shuai Wang; Li-Ming Yang; Dan Cui (Bioresource Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Efficient removal of dissolved tri-n-butyl phosphate from aqueous solution by immobilized bacterial microspheres - Si-Yi Ren; Zhao-Xing Peng; Jin-Ru Feng; Xi-Ming Zeng; Hong-Gang Ni (Journal of Environmental Management, 2025)

Tracing anthropogenic imprints on polybrominated and polychlorinated dibenzo-p-dioxin/furans in soil: A comprehensive field study in an urban agglomeration of China - Ming-Yang Liu; Hui-Ru Li; Ping-An Peng; Ai-Min Song; Yang Li; Fei-Xiang Xie; Yong-Hong Zhang; Jian-Fang Hu (Environmental Research, 2025)

Toward zero-waste phosphogypsum valorization: Reengineered reverse-direct flotation synchronizes gypsum purification and functional co-products production - Ming-Sheng Du; Bo Long; Yi-Zhe Mei; Yong-Shuang Li; Shuang Li; Xue-Qian Wu; Ru-an Chi; Yun-Zhi Tan; Dong-Sheng Li (Chemical Engineering Journal, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

TISCalling: leveraging machine learning to identify translational initiation sites in plants and viruses - Ming-Ren Yen; Ya-Ru Li; Chia-Yi Cheng; Ting-Ying Wu; Ming-Jung Liu (Plant Molecular Biology, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Co-encapsulation and stability evaluation of myricetin and epicatechin in the oxidized starch-coated edible dock protein hydrogels - Si-Qi Li; Zhi-Yuan Yang; Ming Yang; Wei Wang; Yu-Ru Wu; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2025)

Holocene hydroclimatic changes inferred from a mountainous lake sedimentary record on the southeastern Tibetan Plateau - Jianchao Zhou; Jinglu Wu; Ru Guo; Ming Ji (International Journal of Earth Sciences, 2025)

Synthesis of hollow HC-Ni0.96S@MXene/C nanobox as advanced anode for lithium-ion and sodium-ion battery - Song-Yi Liao; Jing Chen; Dao-Ren Deng; Cai-Yun Wu; Selina X. Yao; Yi Wang; Yu-Ming Ru; Xiao-Yan Li; Xu-Gang Shu; Yong-Gang Min (Chemical Engineering Journal, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

First report of Stagonosporopsis pogostemonis causing the fruit rot disease of Capsicum annuum L. in China - Mengting Zou; Banlop Leelahasilp; Ming-Rong Chen; Yu-Ru Wang; Yong Wang (Crop Protection, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Structural and electronic regulation of transition metal borides: from controllable synthesis to industrial alkaline water splitting - Na Xu; Xin-Ru Li; Denghao Ouyang; Guodong Li; Shijian Cheng; Zhongmin Tang; Yong-Ming Chai; Bin Dong (Fuel, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Fast simulation strategy for capacitively-coupled plasmas based on fluid model - Jing-Ze Li; Ming-Liang Zhao; Yu-Ru Zhang; Fei Gao; You-Nian Wang (Computer Physics Communications, 2025)

Effects of imidacloprid on Orius similis: assessing growth, development, and reproduction through age-stage two-sex life table analysis under contact and stomach toxicity treatments - Bo Zhang; Yi-Ru Li; Jin-Long Zhang; Guo-Hua Chen; Nian Yang; Ji-Huan Liu; Guo-Ting Yuan; Xiao-Ming Zhang (Journal of Pest Science, 2025)

Isoalcanivorax beigongshangi sp. nov., isolated from the fermented grains of Chinese baijiu - Tong-Xi Zhang; Yi-Ming Li; Hao-Yue Gu; Ru Zhang; Zhan-Bin Sun; Han-Xu Pan; Qing Ren (Antonie van Leeuwenhoek, 2025)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Targeting PADI2 as a potential therapeutic strategy against metastasis in oral cancer via suppressing EMT-mediated migration and invasion and CCL3/5-induced angiogenesis - Shih-Kai Hung; Chih-Chia Yu; Hon-Yi Lin; Wen-Yen Chiou; Moon-Sing Lee; Ru-Inn Lin; Ming-Chi Lu (Clinical & Experimental Metastasis, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Impacts of food additives on gut microbiota and host health - Ping Li; Ru Qu; Ming Li; Ping Sheng; Liang Jin; Xiaochang Huang; Zhenjiang Zech Xu (Food Research International, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

The construction of yeast β-glucan coated-edible dock protein nanomicelles for the encapsulation and sustained release of apigenin - Qian Zhou; Xiao-Jie Wang; Yu-Ru Wu; Weinan Zhang; Jing Li; Wei Wang; Ying-Nan Liu; Zhen-Yu Yu; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Journal of Food Engineering, 2024)

Bi2O3/Bi@CSs achieved by shock-type heating for fast and long-lasting sodium ion battery - Ya Ru Pei; Xue Jing Yang; Wu Bin Wan; Hai Ming Huang; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2024)

HER2 mutations in advanced cervical neuroendocrine carcinoma: implications for trastuzumab deruxtecan therapy - Wan-Ru Chao; Ming-Yung Lee; Gwo-Tarng Sheu; Yi-Ju Lee; Huang-Pin Shen; Chih-Ping Han (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Biofunctionalized hydrogel composed of genipin-crosslinked gelatin/hyaluronic acid incorporated with lyophilized platelet-rich fibrin for segmental bone defect repair - Er-Yuan Chuang; Yi-Cheng Lin; Yu-Min Huang; Chih-Hwa Chen; Yi-Yen Yeh; Lekha Rethi; Yu-Jen Chou; Pei-Ru Jheng; Jen-Ming Lai; Chang-Jung Chiang; Chin-Chean Wong (Carbohydrate Polymers, 2024)

Evaluating signal bleaching of Al and Ti–Li centers in fluvio-lacustrine sediments of Datong, North China, and its implications for the volcanic eruption chronology - Hao Ji; Chun-Ru Liu; Wen-Peng Li; Chuan-Yi Wei; Bhupati Neupane; Gong-Ming Yin (Quaternary Geochronology, 2024)

Green tea polyphenols reduced Porphyromonas gingivalis virulence and ameliorated aggravated gut inflammation by improving immunity and gut microbiota dysbiosis - Ming Li; Ru Qu; Ping Li; Xuan Mo; Juan Liu; Zhenjiang Zech Xu (Food Bioscience, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Poleward migration of tropical corals inhibited by future trends of seawater temperature and calcium carbonate (CaCO3) saturation - Ya-Yi Huang; Ting-Ru Chen; Kim Phuong Lai; Chao-Yang Kuo; Ming-Jay Ho; Hernyi Justin Hsieh; Yi-Chia Hsin; Chaolun A. Chen (Science of The Total Environment, 2024)

Halogenated aromatic pollutants in routine animal-derived food of south China: Occurrence, sources, and dietary intake risks - Li-Na Zhang; Ping-An Peng; Hui-Ru Li; Ming-Yang Liu; Jian-Fang Hu (Environmental Pollution, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Analytical method for evaluating the tensioned membrane effect in the geosynthetic-reinforced unsaturated embankment soil subjected to localized sinkholes - Hao-ru Zhang; Xiao-qiang Dong; Xi-dong Zhang; Ming-xing Xie (European Journal of Environmental and Civil Engineering, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Adaptive shifts in plant traits associated with nitrogen removal driven by phytoremediation strategies in subtropical river restoration - Yu Xin; Lin Liu; Xiao-Ru Yang; Le-Yang Yang; Shan-Bin Guang; Yu-Ming Zheng; Quan-Bao Zhao (Water Research, 2024)

Natural products from the culture broth of an actinobacteria Streptomyces sp. M5205 and evaluation of their antifungal activity - Jih-Jung Chen; Ming-Jen Cheng; Min Tseng; Ming-Der Wu; Jing-Ru Weng (Phytochemistry Letters, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

A proposed framework for a social-ecological traits database for studying and managing urban plants and assessing the potential of database development using Floras - Chi-Ru Chang; Mong-Huai Su; Yi-Hsuan Li; Ming-Chun Chen (Urban Forestry & Urban Greening, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

Fully space-confined donor-acceptor interaction for highly efficient thermally activated delayed fluorescence emitters - Wen-Cheng Chen; Ming-Hui Zheng; Yu-Lan Wu; Ru-Jia Wang; Jia-Ming Jin; Si-Wei Chen; Bo Liu; Jia-Xiong Chen; Yanping Huo; Shaomin Ji (Chemical Engineering Journal, 2024)

Nitrite acts as the key “switch” governing the free nitrous acid pretreatment in anaerobic digestion: A comprehensive mechanism of abiotic, bioinformatics and bioenergetics effects - Zhibang Han; Ru Fang; Xueting Wang; Guangchen Huang; Dong Wu; Jun Tai; Bing Xie; Yinglong Su; Jingyang Luo; Gang Zhao; Ming Jiang (Chemical Engineering Journal, 2024)

Paleoproterozoic crustal evolution of the Tarim Craton, NW China: Constraints from geochronology and geochemistry of orthogneisses and granitic veins in the Xingdi region of the Quruqtagh Block - Xiao-Hui Sun; Xiang Li; Ru-Xiong Lei; Matthew J. Brzozowski; Hua-Dong Ma; Wei Li; Li-Ming Xiong; Ming-Yi Xia; Chang-Zhi Wu (Precambrian Research, 2023)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

Dietary soybean lecithin promoted growth performance and feeding in juvenile Chinese perch (Siniperca chuatsi) could be by optimizing glucolipid metabolism - Dongliang Wu; Di Peng; Xu-Fang Liang; Ruipeng Xie; Ming Zeng; Junliang Chen; Jie Lan; Ru Yang; Jiacheng Hu; Peisong Lu (Fish Physiology and Biochemistry, 2023)

Recent advances in the unlined cast iron pipe scale characteristics, cleaning techniques and harmless disposal methods: An overview - Ming Li; Dong Zhang; Ru Zhang; Fang Wang; Yang Song; Feiyong Chen; Juan Yang; Changming Li (Chemosphere, 2023)

Mechanisms of swelling inhibition and seepage promotion of weathered crust elution-deposited rare earth ore by hydroxypropyl methyl cellulose - Aoyang Sha; Huifang Yang; Zhengyan He; Qin Zuo; Zhigao Xu; Chenjie Wu; Ming Wu; Ru'an Chi (Minerals Engineering, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Organophosphate esters (OPEs) in a heavily polluted river in South China: Occurrence, spatiotemporal trends, sources, and phase distribution - Yi-Shan Liu; Hui-Ru Li; Zhi-Lang Lao; Sheng-Tao Ma; Zi-Cong Liao; Ai-Min Song; Ming-Yang Liu; You-Sheng Liu; Guang-Guo Ying (Environmental Pollution, 2023)

Dual N-modification enables high-performance Solid-State Li metal batteries with Li5.5PS4.5Cl1.5 - Chaochao Wei; Ru Wang; Zhongkai Wu; Qiyue Luo; Ziling Jiang; Liang Ming; Long Zhang; Hongcheng Lu; Guangshe Li; Liping Li; Chuang Yu; Shijie Cheng (Chemical Engineering Journal, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Decreased levels of perfluoroalkyl substances in patients receiving hemodialysis treatment - Jih-Kai Huang; Yun-Shiuan Chuang; Ping-Hsun Wu; Chi-Jung Tai; Jye-Ru Lin; Mei-Chuan Kuo; Yi-Wen Chiu; Ping-Chi Hsu; Ming-Tsang Wu; Samira Salihovic; Yi-Ting Lin (Science of The Total Environment, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Self-assembly and interaction mechanisms of edible dock protein and flavonoids regulated by the phenolic hydroxyl position - Qian Zhou; Xiao-Jie Wang; Jing Li; Yu-Ru Wu; Wei Wang; Zhen-Yu Yu; Ya-Qing Xiao; Ying-Nan Liu; Shi-Yi Li; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2023)

Highly effective and selective recovery of Gd(III) from wastewater by defective MOFs-based ion-imprinted polymer: Performance and mechanism - Ming yang; Yuxin Zhou; Dandan Zhang; Fang Zhou; Hui Ning; Maoxia He; Ru-an Chi; Weiyan Yin (Chemical Engineering Journal, 2023)

Biosorption and biotransformation behaviours of veterinary antibiotics under aerobic livestock wastewater treatment processes - Chih-Hung Chen; Yi-Chu Chiou; Chao-Lung Yang; Jen-Hung Wang; Wan-Ru Chen; Liang-Ming Whang (Chemosphere, 2023)

Microplastics in coastal farmed oyster (Crassostrea angulata) shells: Abundance, characteristics, and diversity - Chih-Feng Chen; Yun-Ru Ju; Yee Cheng Lim; Ming-Huang Wang; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

Permeability decides the effect of antibiotics on sedimentary nitrogen removal in Jiulong River Estuary - Ru Wan; Lianghao Ge; Bin Chen; Jin-Ming Tang; Ehui Tan; Wenbin Zou; Li Tian; Meng Li; Zongbao Liu; Lijun Hou; Guoyu Yin; Shuh-Ji Kao (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Isolation and identification of 3,4-seco-labdane diterpenoids from Callicarpa nudiflora and investigation of their cytotoxicity against HepG2 cells - Qian-Qian Chen; Ming-Hui Fan; Hong-Tao Xu; Le-Yi Huang; Jin-Ling Liu; Shan-Shan Zhang; Ru-Ru Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Identifying potential toxic organic substances in leachates from tire wear particles and their mechanisms of toxicity to Scenedesmus obliquus - Jie-Ru Jiang; Zhi-Feng Chen; Xiao-Liang Liao; Qian-Yi Liu; Jia-Ming Zhou; Shi-Ping Ou; Zongwei Cai (Journal of Hazardous Materials, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

Chronology analysis of huge landslide based on ESR dating materials on sliding face in carbonate areas of south eastern Tibet - Chun-Ru Liu; Ying-Ying Tian; Hao Ji; Xi Ma; Chuan-Yi Wei; Jia-Xiang Dang; Gong-Ming Yin; Yong-Sheng Zhou; Ren-Mao Yuan (Quaternary Geochronology, 2023)

The effect of metformin and drinking water quality variation on haloacetamide formation during chlor(am)ination of acetaminophen - Ming-Chuan Ho; Ru-Ying Yang; Guan-Fu Chen; Wei-Hsiang Chen (Journal of Environmental Management, 2023)

A single fluorescent probe reveals changes in endoplasmic reticulum–mitochondria contact in hepatocytes during ferroptosis - Ling-Li Wang; Ya-Ru Zhang; Ming-Hua Zheng; Xuan Wang; Xue Wu; Jing-Yi Jin (Chemical Engineering Journal, 2023)

Chemical constituents from Ajuga macrosperma Wall. ex Benth. (Lamiaceae) and their chemotaxonomic significance - Hua-Yi Jiang; Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Ming-Ming Li; Rui Yang; Hong-Ping He (Biochemical Systematics and Ecology, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

A novel oxygen vacancies enriched Co Ni LDO catalyst activated peroxymonosulfate for the efficient degradation of tetracycline - Hao-Liang Jiang; Ming-Hui Li; Ling-Xi Zhao; Zhao-Xing Yan; Meng Xie; Jin-Ming Lin; Ru-Song Zhao (Journal of Water Process Engineering, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

A comprehensive understanding of adaptive thermal comfort in dynamic environments – An interaction matrix-based path analysis modeling framework - Ru Ming; Baizhan Li; Chenqiu Du; Wei Yu; Hong Liu; Risto Kosonen; Runming Yao (Energy and Buildings, 2023)

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Plant identity shapes phyllosphere microbiome structure and abundance of genes involved in nutrient cycling - Jian Li; Ming-Kang Jin; Roy Neilson; Shi-Lin Hu; Yi-Jia Tang; Zhao Zhang; Fu-Yi Huang; Jing Zhang; Xiao-Ru Yang (Science of The Total Environment, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Surface wrinkles enhancing electromagnetic interference shielding of copper coated polydimethylsiloxane: A simulation and experimental study - Qian-Ming He; Jun-Ru Tao; Dian Yang; Yi Yang; Ming Wang (Chemical Engineering Journal, 2023)

Metallurgical performance and structural characteristics of cokes of hypercoal prepared from the mixture of low-rank coal and biomass residue - Jun Zhao; Hong Liu; Haochen Zhang; Xiaolin Song; Haibin Zuo; Guangwei Wang; Zhigao Xu; Ming Wu; Zhenyue Zhang; Ru'an Chi (Fuel, 2023)

Identifying the impact of Fe nanoparticles encapsulated by nitrogen-doped carbon to Fe single atom sites for boosting oxygen reduction reaction toward Zn-air batteries - Wen-Jun Niu; Ying-Yun Yan; Ru-Ji Li; Wei-Wei Zhao; Jiang-Lei Chen; Ming-Jin Liu; Bingni Gu; Wen-Wu Liu; Yu-Lun Chueh (Chemical Engineering Journal, 2023)

Effect of active chilled beam layouts on ventilation performance and thermal comfort under variable heat gain conditions - Ru Ming; Panu Mustakallio; Risto Kosonen; Tuomas Kaukola; Simo Kilpeläinen; Baizhan Li; Yuxin Wu; Runming Yao (Building and Environment, 2023)

Three-dimensional hydroxylated covalent organic frameworks for solid phase extraction of glucocorticoids in environmental water samples - Chuqing Liu; Guiju Xu; Baoyu Li; Xiaoli Wang; Jin-Ming Lin; Ru-Song Zhao (Analytica Chimica Acta, 2023)

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

Two new aromatic derivatives from Codonopsis pilosula and their α-glucosidase inhibitory activities - Ru-Yue Wang; Pan-Jie Su; Bing Li; Xiao-Qing Zhan; Feng-Ming Qi; Chun-Wei Lv; Fang-Di Hu; Kun Gao; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

The Effect of Co-Exposure to Glyphosate, Cadmium, and Arsenic on Chronic Kidney Disease - Junne-Ming Sung; Wei-Hsiang Chang; Kuan-Hung Liu; Chung Yu Chen; Trias Mahmudiono; Wan-Ru Wang; Ho-Chi Hsu; Zhen-Yi Li; Hsiu-Ling Chen (Exposure and Health, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

First report of Capsicum frutescens endornavirus 1 infecting pepper in China - Ming-xia Gong; Hu Zhao; Xing Wu; Meng Wang; Zeng-jing Zhao; Zhi He; Ru-kui Huang; Jing-ping Sun; Ri-sheng Wang (Journal of Plant Pathology, 2022)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

Prediction of Metabolic Disorders Using NMR-Based Metabolomics: The Shanghai Changfeng Study - Qi Wu; Qing-xia Huang; Hai-luan Zeng; Shuai Ma; Huan-dong Lin; Ming-feng Xia; Hui-ru Tang; Xin Gao (Phenomics, 2021)

OsGSTU6 Contributes to Cadmium Stress Tolerance in Rice by Involving in Intracellular ROS Homeostasis - Xiu-Qing Jing; Meng-Ru Zhou; Xiu-Min Nie; Lu Zhang; Peng-Tao Shi; Abdullah Shalmani; Hai Miao; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2021)

Flavobacterium undicola sp. nov., isolated from a freshwater lake - Wen-Ming Chen; Yi-Ru Xie; Soon-Wo Kwon; Shih-Yi Sheu (Archives of Microbiology, 2021)

Distribution and genetic variability of young-of-the-year greater amberjack (Seriola dumerili) in the East China Sea - Takamasa Hasegawa; Ching-Ping Lu; Sheng-Tai Hsiao; Tsubasa Uchino; Hsin-Ming Yeh; Wei-Chuan Chiang; June-Ru Chen; Chiyuki Sassa; Kazuyoshi Komeyama; Ryo Kawabe; Takashi Sakamoto; Satoshi Masumi; et al. (Environmental Biology of Fishes, 2020)
We examined the distribution and genetic variability of the greater amberjack Seriola dumerili in the East China Sea (ECS) from the mitochondrial DNA (mtDNA) control region of young-of-the-year (YOY) individuals, which may reflect the genetic characteristics of the spawning population. In the years 2016 and 2017, a total of 165 YOY S. dumerili were collected from two different locations in the ECS: the southern part of the ECS, and western Japanese coast. The spawning period was estimated using otolith daily increments from a total of 67 larvae and juveniles collected in the ECS. Results from size and age distribution indicated that S. dumerili spawned near the shelf break region in the southern ECS from January to April. Phylogenetic analysis based on mtDNA sequence data showed no significant genetic differentiation among samples collected from different locations, implying S. dumerili in the ECS is mainly composed of one population. S. dumerili around the Japanese coast may be originated from the southern ECS.

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Genome-Wide Identification of Malectin/Malectin-Like Domain Containing Protein Family Genes in Rice and Their Expression Regulation Under Various Hormones, Abiotic Stresses, and Heavy Metal Treatments - Xiu-Qing Jing; Abdullah Shalmani; Meng-Ru Zhou; Peng-Tao Shi; Izhar Muhammad; Yi Shi; Rahat Sharif; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2020)

Isolation, purification and identification of two new alkaloids metabolites from marine-derived Verrucosispora sp. FIM06025 - Ming-Hong Chen; Wen-Long Zhang; Li Chen; Ru Lin; Yang Xie; Dong-Sheng Fang; Yun-Yang Lian; Hong Jiang (Natural Product Research, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Quantification of cardiac pumping mechanics in rats by using the elastance–resistance model based solely on the measured left ventricular pressure and cardiac output - Chih-Hsien Wang; Ru-Wen Chang; En-Ting Wu; Chun-Yi Chang; Hsien-Li Kao; Ming-Shiou Wu; Ya-Jung Cheng; Yih-Sharng Chen; Kuo-Chu Chang (Pflügers Archiv - European Journal of Physiology, 2019)

Exogenous application of gibberellic acid and ascorbic acid improved tolerance of okra seedlings to NaCl stress - Yong-Hui Wang; Gen Zhang; Yuan Chen; Jin Gao; Yan-Ru Sun; Ming-Fa Sun; Jian-Ping Chen (Acta Physiologiae Plantarum, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Efficient generation of functional cardiomyocytes from human umbilical cord-derived virus-free induced pluripotent stem cells - Kai Hong Wu; Su Yun Wang; Qian Ru Xiao; Yu Yang; Ning Ping Huang; Xu Ming Mo; Jian Sun (Cell and Tissue Research, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Differential Inhibition of Nav1.7 and Neuropathic Pain by Hybridoma-Produced and Recombinant Monoclonal Antibodies that Target Nav1.7 - Sangsu Bang; Jiho Yoo; Xingrui Gong; Di Liu; Qingjian Han; Xin Luo; Wonseok Chang; Gang Chen; Sang-Taek Im; Yong Ho Kim; Judith A. Strong; Ma-Zhong Zhang; et al. (Neuroscience Bulletin, 2018)

New phenolic acids from Salvia yunnanensis C.H.Wright - Yun Yu; Yin-ru Wang; Zhen-huan Dong; Wei Li; Shu-Ming Li; Xue-feng Huang (Natural Product Research, 2017)

Characteristic differences in essential oil composition of six Zanthoxylum bungeanum Maxim. (Rutaceae) cultivars and their biological significance - Shu-ming Liu; Shi-jun Wang; Si-yao Song; Yong Zou; Jun-ru Wang; Bing-yin Sun (Journal of Zhejiang University-SCIENCE B, 2017)

Zircon U–Pb dating of eclogite from the Qiangtang terrane, north-central Tibet: a case of metamorphic zircon with magmatic geochemical features - Qing-guo Zhai; Bor-ming Jahn; Xian-hua Li; Ru-yuan Zhang; Qiu-li Li; Ya-nan Yang; Jun Wang; Tong Liu; Pei-yuan Hu; Suo-han Tang (International Journal of Earth Sciences, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

Quantification of 3D macropore networks in forest soils in Touzhai valley (Yunnan, China) using X-ray computed tomography and image analysis - Jia-ming Zhang; Ze-min Xu; Feng Li; Ru-ji Hou; Zhe Ren (Journal of Mountain Science, 2017)

Arabidopsis heat stress transcription factors A2 (HSFA2) and A3 (HSFA3) function in the same heat regulation pathway - Xiao-dong Li; Xiao-li Wang; Yi-Ming Cai; Jia-hai Wu; Ben-tian Mo; Er-ru Yu (Acta Physiologiae Plantarum, 2017)

Collection and aging of greater amberjack Seriola dumerili larvae and juveniles around the Penghu Islands, Taiwan - Takamasa Hasegawa; Hsin-Ming Yeh; June-Ru Chen; Chin-Lau Kuo; Ryo Kawabe; Yoshitaka Sakakura (Ichthyological Research, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Temporal properties of dual-peak responses of mouse retinal ganglion cells and effects of inhibitory pathways - Ru-Jia Yan; Hai-Qing Gong; Pu-Ming Zhang; Shi-Gang He; Pei-Ji Liang (Cognitive Neurodynamics, 2016)

Cytomolecular characterization and origin of de novo formed maize B chromosome variants - Ya-Ming Cheng; Ying-Ru Feng; Yao-Pin Lin; Shu-Fen Peng (Chromosome Research, 2016)

Genetic Diversity and Population Structure Patterns in Chinese Cherry (Prunus pseudocerasus Lindl) Landraces - Tao Chen; Xiao-jiao Huang; Jing Zhang; Qing Chen; Yin Liu; Hao-ru Tang; Dong-ming Pan; Xiao-rong Wang (Plant Molecular Biology Reporter, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Deficient and excess dietary selenium levels affect growth performance, blood cells apoptosis and liver HSP70 expression in juvenile yellow catfish Pelteobagrus fulvidraco - Jun-Ru Hu; Yan-Hua Huang; Guo-Xia Wang; Ying-Xia Wu; Jian-An Xian; An-Li Wang; Jun-Ming Cao (Fish Physiology and Biochemistry, 2016)

Dormancy release of Cotinus coggygria seeds under a pre-cold moist stratification: an endogenous abscisic acid/gibberellic acid and comparative proteomic analysis - Zhi Jun Deng; Xiao Fang Hu; Xun Ru Ai; Lan Yao; Shi Ming Deng; Xin Pu; Song Quan Song (New Forests, 2016)

Di-(2-ethylhexyl) phthalate accelerates atherosclerosis in apolipoprotein E-deficient mice - Jin-Feng Zhao; Sheng-Huang Hsiao; Ming-Hua Hsu; Kuan-Chuan Pao; Yu Ru Kou; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Environmental Enrichment Ameliorates Neonatal Sevoflurane Exposure-Induced Cognitive and Synaptic Plasticity Impairments - Mu-huo Ji; Xing-ming Wang; Xiao-ru Sun; Hui Zhang; Ling-sha Ju; Li-li Qiu; Jiao-jiao Yang; Min Jia; Jing Wu; Jianjun Yang (Journal of Molecular Neuroscience, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Rapid development of tissue bank achieved by International Atomic Energy Agency (IAEA) Tissue Banking Programme in China - Yu-Min Zhang; Jian-Ru Wang; Nai-Li Zhang; Xiao-Ming Liu; Mo Zhou; Shao-Ying Ma; Ting Yang; Bao-Xing Li (Cell and Tissue Banking, 2014)

Synthesis, biological evaluation and molecular modeling studies of Schiff bases derived from 4-methylsalicylic acid as potential immunosuppressive agents - Ru Yan; Peng-Gang Liu; Zhi-Ming Zhang; Xian-Ying Fang; Xue-Wei Zhang; Jia-Li Deng; Hai-Liang Zhu (Medicinal Chemistry Research, 2013)

Circulating microparticles in patients with coronary heart disease and its correlation with interleukin-6 and C-reactive protein - Ying Cui; Lihui Zheng; Ming Jiang; Ru Jia; Xiao Zhang; Qishan Quan; Guiqin Du; Dongjin Shen; Xiaodan Zhao; Wenying Sun; Hongwei Xu; Lijuan Huang (Molecular Biology Reports, 2013)

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

Physiological roles of mycothiol in detoxification and tolerance to multiple poisonous chemicals in Corynebacterium glutamicum - Ying-Bao Liu; Ming-Xiu Long; Ya-Jie Yin; Mei-Ru Si; Lei Zhang; Zhi-Qiang Lu; Yao Wang; Xi-Hui Shen (Archives of Microbiology, 2013)

Protective effect of hydrogen-rich saline on ischemia/reperfusion injury in rat skin flap - Ling Zhao; You-bin Wang; Shi-rui Qin; Xue-mei Ma; Xue-jun Sun; Ming-lian Wang; Ru-gang Zhong (Journal of Zhejiang University-SCIENCE B, 2013)

Role of hydrogen peroxide and antioxidative enzymes in Pinus tabulaeformis seedlings inoculated with Amanita vaginata and/or Rhizoctonia solani - Ru-Qin Zhang; Ming Tang (European Journal of Plant Pathology, 2012)

Genetic surface-display of methyl parathion hydrolase on Yarrowia lipolytica for removal of methyl parathion in water - Xing-Xing Wang; Zhe Chi; Shao-Guo Ru; Zhen-Ming Chi (Biodegradation, 2012)

The mitochondrial genome of the quiet-calling katydids, Xizicus fascipes (Orthoptera: Tettigoniidae: Meconematinae) - MING RU YANG; ZHI JUN ZHOU; YAN LIN CHANG; LE HONG ZHAO (Journal of Genetics, 2012)

Increased function of the TRPV1 channel in small sensory neurons after local inflammation or in vitro exposure to the pro-inflammatory cytokine GRO/KC - Fei Dong; Yi-Ru Du; Wenrui Xie; Judith A. Strong; Xi-Jing He; Jun-Ming Zhang (Neuroscience Bulletin, 2012)

Clozapine Protects Dopaminergic Neurons from Inflammation-Induced Damage by Inhibiting Microglial Overactivation - Xiaoming Hu; Hui Zhou; Dan Zhang; Sufen Yang; Li Qian; Hung-Ming Wu; Po-See Chen; Belinda Wilson; Hui-Ming Gao; Ru-band Lu; Jau-Shyong Hong (Journal of Neuroimmune Pharmacology, 2012)

Reactive oxygen species-mediated PKC and integrin signaling promotes tumor progression of human hepatoma HepG2 - Chi-Tan Hu; Jia-Ru Wu; Chuan-Chu Cheng; Sindy Wang; Hsiao-Ting Wang; Ming-Che Lee; Ling-Jung Wang; Siou-Mei Pan; Tsu-Yao Chang; Wen-Sheng Wu (Clinical & Experimental Metastasis, 2011)

MpAsr encodes an intrinsically unstructured protein and enhances osmotic tolerance in transgenic Arabidopsis - Jin-Ran Dai; Bing Liu; Dong-Ru Feng; Hai-yan Liu; Yan-ming He; Kang-biao Qi; Hong-Bin Wang; Jin-Fa Wang (Plant Cell Reports, 2011)

Influence of dhaT mutation of K. pneumoniae on 1,3-propanediol fermentation - Yun-Zhen Xu; Ru-Chun Wu; Zong-Ming Zheng; De-Hua Liu (World Journal of Microbiology and Biotechnology, 2011)

Comparison of Non-covalent Interactions Between a Series of N-Phosphoryl Dipeptide or Methyl Esters and Protein by Electrospray Ionization Mass Spectrometry - Li-ming Qiang; Ming-xiu Lü; Xu-ru Dong; Shu-xia Cao; Kui Lu; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2011)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

The CAG repeat in SCA12 functions as a cis element to up-regulate PPP2R2B expression - Chih-Hsin Lin; Chiung-Mei Chen; Yi-Ting Hou; Yih-Ru Wu; Hsiu-Mei Hsieh-Li; Ming-Tsan Su; Guey-Jen Lee-Chen (Human Genetics, 2010)

Detection of circulating tumor cells in peripheral blood from patients with gastric cancer using microRNA as a marker - Hui Zhou; Jun-Ming Guo; Yan-Ru Lou; Xin-Jun Zhang; Fa-De Zhong; Zhen Jiang; Jia Cheng; Bing-Xiu Xiao (Journal of Molecular Medicine, 2010)

A Series of Novel Rare Earth Molybdotungstosilicate Heteropolyoxometalates Binding to Bovine Serum Albumin: Spectroscopic Approach - Yan-Jun Hu; Yu Ou-Yang; Ai-Min Bai; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

Livin abrogates apoptosis of SPC-A1 cell by regulating JNKI signaling pathway - Yu-Sheng Chen; Hong-Ru Li; Ming Lin; Gang Chen; Bao-Song Xie; Neng-Luan Xu; Li-Fang Lin (Molecular Biology Reports, 2010)

Biological Activation of Heteropoly Complex of Molybdotungstosilicate Containing Lanthanum K10H3La(SiMo6W5O39)2⋅26H2O: Spectroscopic Approach and Microcalorimetry - Yan-Jun Hu; Yu Ou-Yang; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

Solid-state fermentation of cornmeal with the ascomycete Morchella esculenta for degrading starch and upgrading nutritional value - Gui-Ping Zhang; Feng Zhang; Wen-Ming Ru; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2010)

A new iridoid glycoside from Scrophularia ningpoensis - Zheng-Rui Niu; Ru-Feng Wang; Ming-Ying Shang; Shao-Qing Cai (Natural Product Research, 2009)

Origin of the Gangdise (Transhimalaya) Permian arc in southern Tibet: Stratigraphic and volcanic geochemical constraints - Quan‐Ru Geng; Zhi‐Ming Sun; Gui‐Tang Pan; Di‐Cheng Zhu; Li‐Quan Wang (Island Arc, 2009)
The well‐studied Mesozoic and Cenozoic volcanic rocks of the Gangdise Terrane, southern Tibet, are widely interpreted to have resulted from subduction of the Neotethys; however, Late Paleozoic volcanic rocks and their tectonic setting remain poorly studied. Based on new geological data, we carried out stratigraphical and geochemical analyses of Permian volcano‐stratigraphic sequences within an east–west‐trending, fault‐bounded zone of uplift in the central Gangdise Terrane. Sedimentary rocks in this area consist of platform carbonates and terrigenous clastic rocks that represent widespread shallow‐marine sedimentary basins developed around northern Gondwana. A regression or tectonic uplift event is recorded in Permian sedimentary rocks that show the local development of fluvial environments. The sedimentary succession contains evidence of two volcanic stages: a period of basaltic extrusions and younger explosive felsic magmatism. The first volcanic stage is Early and Middle Permian in age. Tholeiitic basaltic lavas are exposed around Maizhokunggar (Tangjia) and Lhunzhub in central Gangdise. The Lower Permian basalts are relatively enriched in MgO (4.58–12.19%), whereas the Middle Permian basalts are characterized by high Al 2 O 3 contents (11.75–21.22%). Rocks of both ages are enriched in large‐ion lithophile elements (LILE) and light rare earth elements (LREE), and show pronounced negative Nb and Ta anomalies. Total REE contents and light (LREE)/heavy (HREE) ratios increased from the Early to Middle Permian. Observed variations in initial Sr, Nd, and Pb isotopes ( 87 Sr/ 86 Sr i = 0.7013–0.7066, 207 Pb/ 204 Pb i = 15.53–15.63, and 208 Pb/ 204 Pb i = 38.04–38.64 for a given 206 Pb/ 204 Pb i ; εNd = +0.69 to −11.55) can be explained by crustal interaction with mantle sources, as is characteristic of metasomatism by slab‐derived fluids or assimilation and fractional crystallization (AFC) processes during magmatic evolution. The observed geochemical signatures, coupled with stratigraphic constraints, support the hypothesis that an initial arc formed during the Permian due to southward subduction of the Paleotethys, predating the well‐known Mesozoic arc preserved in the Gangdise Terrane.

The Relation Between Oxygen Consumption and the Equilibrated Inspired Oxygen Fraction in an Anesthetic Circle Breathing System: A Mathematic Formulation & Laboratory Simulations - Tsai-Hsin Chen; Chung-Han Hsin; Wen-Ru Ko; Cher-Ming Liou; Wei-Te Hung (Annals of Biomedical Engineering, 2009)

Effects of ginkgolide B on neuronal discharges in paraventricular nucleus of rat hypothalamic slices - Yue Lin; Ru Wang; Xin Wang; Rui-Rong He; Yu-Ming Wu (Neuroscience Bulletin, 2008)

Induced hydrolytic enzymes of ectomycorrhizal fungi against pathogen Rhizoctonia solani - Ming Tang; Ru-Qin Zhang; Hui Chen; Hai-Han Zhang; Zhi-Qiang Tian (Biotechnology Letters, 2008)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Histidines 345 and 378 of Bacillus stearotheromophilus leucine aminopeptidase II are essential for the catalytic activity of the enzyme - Guang-Yuh Hwang; Lih-Ying Kuo; Ming-Ru Tsai; Shin-Ling Yang; Long-Liu Lin (Antonie van Leeuwenhoek, 2005)

Expression of an antibody-targeted plasminogen activator in Escherichia coli using chemically induced stress responses - Ming Yu; Meimin Yu; Binggen Ru (Biotechnology Letters, 2004)

Enhanced expression of an antibody-targeted plasminogen activator in Escherichia coli by fusion to decorsin - Ming Yu; Meimin Yu; Binggen Ru (Biotechnology Letters, 2004)

In Vivo and In Vitro Inhibitions of Red Drum (Sciaenops ocellatus) Brain Acetylcholinesterase and Liver Carboxylesterase by Monocrotophos at Sublethal Concentrations - Shaoguo Ru; Xuanhui Wei; Ming Jiang; Yongqi Li (Water, Air, & Soil Pollution, 2003)

The effect of lanthanide chloride on abscisic acid and electron-transport activity of some crops - Fu Li Zeng; Ming Feng Zhang; Shao Min Zhou; Ji Gui Wu; Ru Wen Deng (Biological Trace Element Research, 1999)